Evaluation of Adhesions Induced Intestinal Obstruction following Abdominal Penetrating Missile Injuries - Al-Atroshi, . Mohammed A.; Akram, Warqaa Mazin; Farouk, Bassam (AL-Kindy College Medical Journal, 2009)
Objectives: To evaluate the incidence of adhesionsinduced intestinal obstruction after explorative laparotomydue to bullet/shell injury in Al-Kindi teachinghospital/Baghdad.Results: Thirty-six out of the 76 cases with adhesionsinduced intestinal obstruction (A.I.I.O.) had history oflaparotomy for penetrating missile injury, 26 of them wereexplored as a method of management of A.I.I.O. withmean age (22 for those explored, ٣٧ for those treatedconservatively), 16 of them presented within a year or lessfrom the previous surgery.Methods: Comparative interventional prospective study ofcases with adhesions induced intestinal obstructionadmitted to the surgical wards in Al-Kindi teachinghospital from the 1st of January 2008 to 31st of December2008. cases were followed considering the indications ofprevious laparotomies, the patients age, gender, durationbetween previous surgery and their presentation withintestinal obstructionConclusion: Cases required surgical interventions fortreatment were mainly those following explorativelaparotomy for penetrating missile injury they were mainlyof young age Groups